Faktor-Faktor yang Berhubungan dengan Perilaku Penggunaan APD Tenaga Kesehatan di PT Kereta Commuter Indonesia - Amelia Anggraini; Ernyasih (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aims to determine factors including age, gender, education, tenure, and knowledge associated with the PPE use behavior of health workers at PT Kereta Commuter Indonesia. The study was conducted using a cross-sectional design with a quantitative approach. The sample consisted of 60 employees of the PT Kereta Commuter Indonesia Health Unit selected through total sampling. Primary data was collected using a questionnaire of OHS knowledge and behavior including age, gender, education, tenure and knowledge. Data analysis was performed by chi square test with the limit of significance used (P < 0.05). A total of 91.7% of health workers aged 18-35 years and as many as 98.3% of health workers had good knowledge by univariate analisys. There is a significant relationship between the age factor and the PPE use behavior of health workers with the results (p=0.039) and the knowledge factor with the PPE use behavior of health workers with the results (p=0.006). Age and knowledge of health workers at PT Kereta Commuter Indonesia have an influence on PPE use behavior. The company needs to develop programmed education and training, including supervision, monitoring and evaluation activities by management to increase motivation for implementing OSHs culture.